112 RNA Sequencing Analysis of Endothelium in a Patient-Specific Intracranial Aneurysm Model. (April 2023) - Samarage, Hasitha Milan; Kaneko, Naoki
Abstract : INTRODUCTION: Ruptured intracranial aneurysms are responsible for 5-10% of all strokes yet can carry a mortality rate as high as 50%. The growth and rupture of aneurysms is a consequence of complex arterial wall remodeling resulting from complex interactions between cellular biological processes METHODS: A total of eight aneurysm casts were created from patients' 3D rotational angiographic data in our institution's database. Models represented two morphologies (bifurcation and sidewall aneurysms), four locations (middle cerebral artery bifurcation, basilar tip bifurcation, internal cerebral artery-posterior communicating artery sidewall, internal cerebral artery-superior hypophyseal artery sidewall), and two clinical conditions (stable aneurysms and growing aneurysms). The lumen were coated with fibronectin, connected to a pump infusing a cell suspension of HUVEC cells. After culturing to achieve confluence, specimens from the aneurysm and parent artery were separately cut to extract RNA used for sequencing. RESULTS: A total of 358 DEGs were identified between aneurysm and parent vessel, 222 DEGs were identified between sidewall and bifurcation aneurysm morphologies and 20437 DEGs were identified between growing and stable aneurysms. Genes such as SYNPO, CHSY3 ALKBH8 were found to be upregulated in endothelial cells within the aneurysms while genes such as FABP4, ANGPT2, SMAD6 and ADAMTS18 were found to be downregulated in comparison with endothelial cells within the parent artery. SERPINB6 was found to be upregulated and FOXN2 was found to be downregulated in growing aneurysms compared to stable aneurysms. CONCLUSIONS: We demonstrate the successful development of a patient specific, in-vitro pulsatile intracranial aneurysm cell culture model which can be used to study the complex interactions of endothelial cell biology, specifically the unique transcriptomic profiles of various endothelial cell populations that are subject to varying hemodynamic conditions based on location within the vasculature